Drug Related Problems in Diabetic Patients with Medication Reconciliation Process in Saraburi Hospital - Nontawong, Supreeda; Manyam, Chutipapha; Munprom, Chaowarat (Journal of Health Science of Thailand, 2017)
Pharmaceutical care in diabetic patients, for accuracy and safety in medication use, has adopted ‘medication reconciliation process’ which is the process of obtaining the most current medication list from patients in order to minimize duplication use and to reduce undesirable symptoms from medication which the patients were taking. The study also investigated and followed up patients’ cooperation in using medication for reducing blood sugar level, in the groups of diabetic patients from both outpatient department and inpatients who received medication prescription before discharge and then returned for follow-up appointments at the diabetic clinic. The study applied descriptive research methodology by selecting diabetic patients, who had blood sugar levels of 160 mg% or higher with medication list of more than 5 items and regularly returned for medical appointments at the diabetic clinic, to participate in receiving pharmaceutical care in order to follow up and investigate problems and their cooperation in using medication. The follow up and investigation study, relating to problem with patients’ cooperation in using medication, was conducted on diabetic patients who visited the diabetic clinic during 9.00-11.30 hours on every Wednesday and Friday from 1st November 2009 to 28th February 2011. There were a total of 578 diabetic patients selected for pharmaceutical care, of which 277 cases were found to have problems with their cooperation in using correct medication. The study showed that 27 percent of the cases used lower dosage than the prescription; 22 percent of the cases were found to have problem with irregular oral pill taking or injection; 18.05 percent of the cases did not take medication or injection on time; 17.33 percent of the cases had problem with incorrect injection (higher/lower than prescribed dose); 6.17 percent of the cases stopped taking oral pills or injection; 4.6 percent of the cases used higher dose than doctor’s prescription and 3.97 percent did not turn up on doctors’ appointments. The study found that the major problem related to patients’ noncompliance with the medication prescription. Pharmacists should emphasize and ensure that the patients understand the importance of correct practice in order for them to change their medication use behaviors which would enhance the effectiveness of continuous medical treatment.